Brazilian anti-indigenous politics: tracking changes on indigenous rights regulation during Bolsonaro’s government / A política anti-indígena brasileira: mudanças nos direitos dos povos indígenas durante o governo Bolsonaro - Gonçalves, Veronica Korber; Cafrune, Marcelo Eibs (Revista Direito e Práxis, 2023)
DOI:10.1590/2179-8966/2023/73123i. Abstract Between 2019 and 2022, the Bolsonaro’s government propagated a strong anti-environmental and anti-indigenous rhetoric that devalued how indigenous peoples live and occupy these territories. In this paper, we are interested in understanding the total repercussions of Bolsonaro’s anti-environmentalism, focusing on the legal norm propositions involving indigenous peoples and indigenous lands. We argue that the Law is one crucial instrument to maintain or change social relations and by tracing normative changes, we can comprehend important aspects of power disputes in specific contexts. In this sense, we examine the production of legal norms by the federal government and by the National Congress that flexibilize, sometimes indirectly, the territorial rights of indigenous peoples and how this process is publicly defended by the contestation of indigenous history, culture, and rights. Keywords: Indigenous peoples; Brazil; Territorial rights; Mining; Indigenous rights; Anti-environmental policies; Anti-indigenous policies; Bolsonaro. Resumo Entre 2019 e 2022, o governo Bolsonaro propagou uma forte retórica antiambiental e antiindígena que desvalorizou a forma como os povos indígenas vivem e ocupam esses territórios. Neste trabalho, nos interessa compreender a repercussão total do antiambientalismo de Bolsonaro, com foco nas proposições de norma jurídica envolvendo povos indígenas e terras indígenas. Argumentamos que o Direito é um instrumento crucial para manter ou alterar as relações sociais e, ao traçar mudanças normativas, podemos compreender aspectos importantes das disputas de poder em contextos específicos. Nesse sentido, examinamos a produção de normas legais pelo governo federal e pelo Congresso Nacional que flexibilizam, por vezes de forma indireta, os direitos territoriais dos povos indígenas e como esse processo é defendido publicamente pela contestação da história, cultura e direitos indígenas . Palavras-chave: Povos indígenas; Brasil; Direitos territoriais; Mineração; Políticas antiambientais; Políticas anti-Indígenas; Bolsonaro.